Incidence of Subsequent Hip Fracture and Mortality in Elderly Patients: A Multistate Population‐Based Cohort Study in Eastern Spain. (19th May 2022) - Llopis‐Cardona, Fran; Armero, Carmen; Hurtado, Isabel; García‐Sempere, Aníbal; Peiró, Salvador; Rodríguez‐Bernal, Clara L; Sanfélix‐Gimeno, Gabriel
ABSTRACT: Osteoporotic hip fractures in older people may confer an increased risk of subsequent hip fractures and death. The aim of this study was to estimate the cumulative incidence of both recurrent hip fracture and death in the Valencia region. We followed a cohort of 34, 491 patients aged ≥65 years who were discharged alive from Valencia Health System hospitals after an osteoporotic hip fracture between 2008 and 2015, until death or end of study (December 31, 2016). Two Bayesian illness‐death models were applied to estimate the cumulative incidences of recurrent hip fracture and death by sex, age, and year of discharge. We estimated 1‐year cumulative incidences of recurrent hip fracture at 2.5% in women and 2.3% in men, and 8.3% and 6.6%, respectively, at 5 years. Cumulative incidences of total death were 18.3% in women and 28.6% in men at 1 year, and 51.2% and 69.8% at 5 years. One‐year probabilities of death after recurrent hip fracture were estimated at 26.8% and 43.8%, respectively, and at 57.3% and 79.2% at 5 years. Our analysis showed an increasing trend in the 1‐year cumulative incidence of recurrent hip fracture from 2008 to 2015, but a decreasing trend in 1‐year mortality. Male sex and age at discharge were associated with increased risk of death. Women showed higher incidence of subsequent hip fracture than men although they were at the same risk of recurrent hip fracture. Probabilities of death after recurrent hip fracture were higher than those observed in the general population. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).